The Effectiveness of Collaborative Learning Throughtechniques on Group Investigation and Think Pair Share Students' Critical Thinking Ability on Chemical Equilibrium Material - Fauzi, Fajrina; Erna, Maria; Linda, Roza (FKIP-Universitas Riau, 2021)
The purpose of this study was to determine the differences in the improvement of students' thinking skills using collaborative learning techniques Think-Pair-Share and Group Investigation. The research used was a quasi-experimental research design with non equivalent control posttest design. The data collection technique used critical thinking skills questions consisting of 5 essay test questions. Based on the research results of hypothesis testing using paired simple t-test , the results obtained were sig (2-tailed) <0.05, which means that collaborative learning of GI and TPS techniques is effective on critical thinking skills than the control class. Hypothesis testing is to see significant differences between collaborative learning. TPS and GI techniques used independent sample t-test and the results obtained were sig (2-tailed) <0.05, which means that there is a significant difference between collaborative learning of GI and TPS techniques on critical thinking skills. For the average percentage of critical thinking skills in the collaborative learning class, the Think-Pair-Share technique is 80.57% and Group Investigation is 76.73%, and in the control class it is 68.45%, which means the application of collaborative learning techniques Think-Pair- Share is more effectively used in improving students' critical thinking skills on chemical equilibrium material.